Crisis management and public policy : Singapore's approach to economic resilience - Sng, Hui Ying; Chia, Wai Mun (Singapore ; Hackensack, NJ : World Scientific Pub. Co.)
"One of the key themes of this book is to study economic crises and financial crises, and the policy measures that are available to manage them. The second key theme of the book is to review several public policies in Singapore, such as competition, healthcare, training, free trade agreements, state capitalism and inequality."--Publisher's description.